Synthesis of Heterocycles via Metal-Catalyzed Reactions that Generate One or More Carbon-Heteroatom Bonds - Wolfe, John P. (Topics in Heterocyclic Chemistry,)
John P. Wolfe Synthesis of Saturated Heterocycles via Metal-Catalyzed Alkene Carboamination or Carboalkoxylation Reactions Sherry R. Chemler, David A. Copeland Synthesis of Saturated Heterocycles via Metal-Catalyzed Alkene Diamination, Aminoalkoxylation, or Dialkoxylation Reactions Wanbin Zhang Synthesis of Heterocycles via Metal-Catalyzed Wacker-Type Oxidative Cyclization Reactions of Alkoxy- or Amino-Alkenes Lisa D. Julian Synthesis of Saturated Heterocycles via Metal-Catalyzed Hydroamination or Hydroalkoxylation Reactions Aaron Aponick, John M. Ketcham Synthesis of Saturated Heterocycles via Metal-Catalyzed Allylic Alkylation Reactions Mark Lautens Synthesis of Heterocycles via Metal-Catalyzed Cascade/Domino Reactions that Generate a C–N or C–O Bond Jerome Waser Synthesis of Saturated Heterocycles via Metal-Catalyzed Formal Cycloaddition Reactions that Generate a C–N or C–O Bond